A study in Scarlet: A Sherlock Holmes adventure - Doyle, Arthur Conan (London : William Collins, 2014)
HarperCollins is proud to present its new range of best-loved, essential classics.
Keywords: Detective and mystery fiction; Detective and mystery stories; Fiction